Anomalous Scientific Foundations: Research and Development (R&D) Model Synthesis Practices in Indonesian Doctoral Dissertations - Tampa, Alimuddin; Chen, Wen Haw; Rosidah; Alimuddin, Fauziyyah (MaPan : Jurnal Matematika dan Pembelajaran, 2025)
The synthesis of Research and Development (R&D) models in Indonesian doctoral dissertations has become increasingly common. This study examines how doctoral students formulate and implement such syntheses, identifying the conceptual and technical challenges they face. Using a concurrent mixed methods design, data were collected through an online survey with open and closed ended questions. Responses from 51 participants were analyzed using descriptive statistics and thematic analysis. The results show that all students used synthesized R&D models without adequate scientific justification, as evidenced by the absence of philosophical grounding, lack of expert validation, misalignment with research paradigms, and omission of preliminary testing. Students also faced three major challenges: limited understanding of philosophical assumptions, difficulty integrating model structures, and strong dependence on informal supervisory advice. These issues undermine methodological coherence and threaten the integrity of developmental research in doctoral programs. The study highlights the need to strengthen methodological training, reform supervision practices, and produce clearer, evidence based guidelines. It recommends prioritizing rigorously validated single model R&D approaches to ensure conceptual clarity and academic credibility. Abstrak: Sintesis model Research and Development (R&D) dalam disertasi doktor di Indonesia semakin meluas. Penelitian ini mengkaji bagaimana mahasiswa doktoral merumuskan dan menerapkan sintesis tersebut serta mengidentifikasi tantangan konseptual dan teknis yang mereka hadapi. Dengan menggunakan desain concurrent mixed methods, data dikumpulkan melalui survei daring yang terdiri atas pertanyaan terbuka dan tertutup. Sebanyak 51 respons dianalisis menggunakan statistik deskriptif dan analisis tematik. Hasil penelitian menunjukkan bahwa seluruh mahasiswa menggunakan model R&D tersintesis tanpa justifikasi ilmiah yang memadai, ditandai dengan ketiadaan landasan filosofis, tidak adanya validasi ahli, ketidaksesuaian dengan paradigma penelitian, dan tidak dilakukannya preliminary testing. Mahasiswa juga mengalami tiga tantangan utama: keterbatasan pemahaman tentang asumsi filosofis, kesulitan mengintegrasikan struktur model, serta ketergantungan yang tinggi pada bimbingan informal dari pembimbing. Masalah-masalah ini melemahkan koherensi metodologis dan mengancam integritas tradisi penelitian pengembangan di program doktor. Penelitian ini menekankan perlunya penguatan pelatihan metodologi, reformasi praktik pembimbingan, dan penyusunan panduan berbasis bukti yang lebih jelas. Penelitian ini merekomendasikan penggunaan model R&D tunggal yang telah divalidasi secara ketat untuk memastikan kejelasan konseptual dan kredibilitas akademik.